PENGARUH BELANJA MODAL, PMDN DAN PMA TERHADAP PERTUMBUHAN EKONOMI DI PULAU SUMATERA - Hanifa Turrahmah; Yulhendri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Economic growth across provinces in Sumatra continues to show disparities, even though the region plays a strategic role in Indonesia's economy and relies on government fiscal spending as well as domestic and foreign investment flows to drive development. This study aims to analyze the impact of capital expenditure, domestic investment (PMDN), and foreign investment (PMA) on economic growth in Sumatra during the 2017–2023 period. The study utilizes panel data from ten provinces in Sumatra, analyzed using the panel data regression method with a Common Effect model. The results indicate that, individually, capital expenditure has a positive and significant effect on economic growth, whereas domestic and foreign investments have negative and insignificant effects. Simultaneously, the three independent variables do not significantly affect economic growth, and the model's explanatory power regarding variations in economic growth is low. These findings suggest that economic growth in Sumatra is driven primarily by government fiscal instruments—specifically capital expenditure—while domestic and foreign private investments have yet to make an optimal contribution; consequently, more targeted policies are needed to enhance the effectiveness of private investment in the region.